Effects of Fodder and Sericin Degumming Agents on Asunder Filament of Golden Silkworm Cocoon of Cricula trifenestrata Helf - Terry M Frans (Jurnal Ilmu Kehutanan)
The research aim was to obtain the effect of fodder and sericin degumming agents on asunder filament of golden silkworm cocoon of Cricula trifenestrata Helf. This study expected to find an asunder filament technology in the yarn spinning phase, as the material of silk textile. The complete random design was used to find the interaction between two treatment factors of fodder types and sericin degumming agents. The length of asunder filament per cocoon (cm), the amount of pieces of asunder filament per cocoon (sheet), and the length of filament per piece (cm/sheet) were evaluated. The combination between avocado leaf and soap sericin degumming agent with wood ashes treatment showed the best results on the average of the length of sericin emitec filament asunder per cocoon, the average amount of filament pieces per cocoon, and the average filament length per piece. Therefore, the treatment combination is recommended on the cocoon asunder process.